2020
DOI: 10.2147/opth.s288224
|View full text |Cite
|
Sign up to set email alerts
|

<p>MOG-IgG- versus AQP4-IgG-Positive Optic Neuritis in Thailand: Clinical Characteristics and Long-Term Visual Outcomes Comparison</p>

Abstract: Purpose: To compare demographic data, clinical and radiological characteristics, treatment, and long-term visual outcomes between myelin oligodendrocyte glycoprotein autoantibodypositive optic neuritis (MOG-IgG + ON) and aquaporin-4 autoantibody-positive optic neuritis (AQP4-IgG + ON) in Thailand. Patients and Methods: We included individuals who were diagnosed with either MOG-IgG + ON or AQP4-IgG + ON over an 11-year period. Demographic data, clinical and radiological characteristics at ON presentation, treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“… 21 Furthermore, severe headache was reported in 75% of the ON cases and had already been described in prior reports on MOGAD. 22 23 24 Oftentimes headache preceded the onset of visual loss by some days or even weeks, was reported as intense and migraine-like, and usually responded well to steroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Furthermore, severe headache was reported in 75% of the ON cases and had already been described in prior reports on MOGAD. 22 23 24 Oftentimes headache preceded the onset of visual loss by some days or even weeks, was reported as intense and migraine-like, and usually responded well to steroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Eye pain may be common in MOG-ON, reported in 73-92% of cases internationally [42,43,48,51,56,57]. In comparative studies, this proportion has been shown to be greater than in AQP4-ON (28-50%) and seronegative ON, including MS (10-46%) [48,51,58]. The majority of eye pain in MOG-ON is pain related to eye movement, with periocular pain being less common [56,57].…”
Section: Eye Painmentioning
confidence: 99%
“…The presence of severe optic disc swelling and peripapillary haemorrhage in the setting of ON is highly suggestive of MOG-ON. Optic disc swelling visible on fundoscopy has been reported in 45-92% of cases of MOG-ON across various international cohorts [22,[43][44][45][47][48][49][50][51][52], and is an important diagnostic clue when assessing patients with ON. This is far more common than the frequencies reported in AQP4-ON (7-52%) [44,48,50,51], and MS-ON (11-14%) [49,51].…”
Section: Optic Disc Swellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of AQP4-IgG has improved our understanding of CNS demyelinating disease and expanded the recognition of the clinical phenotype (5). Furthermore, AQP4-IgG provides the diagnostic criteria; AQP4-IgG positivity in NMOSD implies poor visual prognosis after ON as compared with multiple sclerosis and myelin oligodendrocyte glycoprotein antibody–associated disorders (6–12).…”
mentioning
confidence: 99%